Inhibition of Spiral Growth and Dissolution at the Brushite (010) Interface by Chondroitin 4-Sulfate - Zhai, H.; Wang, L.; Putnis, Christine (American Chemical Society, 2019)
Modulation of mineralization and demineralization of calcium phosphates (Ca-Ps) with organic macromolecules is a critical process which prevents human kidney stone disease. As a long unbranched polysaccharide of urinary glycosaminoglycans, chondroitin 4-sulfate (Ch4S) has been shown to play an essential role in inhibiting the formation of kidney stones. However, the mechanism of the role of Ch4S remains poorly understood. Here, we used in situ atomic force microscopy to observe the growth and dissolution of spirals on brushite (CaHPO4·2H2O) (010) surfaces. The results show that Ch4S preferentially inhibits the [101]Cc step growth/dissolution by step pinning. This step-specific effect appears to be related to specific binding of Ch4S to Ca sites, as the observed inhibition is not seen in other crystallographic directions where there are fewer Ca terminations. Moreover, Ch4S promotes an increase in the terrace width of [101]Cc by the modification of the interfacial energies of the step edge. These in vitro direct observations of Ch4S modulating brushite mineralization and demineralization reveal a dual control of both step kinetics and interfacial energy.